Evaluation of Accuracy of Intraoperative Frozen Section and Imprint Cytology in Gynecological Neoplasms—A Descriptive Cross-Sectional Study of 50 Cases in Tertiary Care Center - Kediya, Ayushi; Shirazi, Nadia; Nautiyal, Ruchira (Journal of Laboratory Physicians, 2023)
Aims and Objectives Gynecological neoplasms are among the most common cancers in female population of India and worldwide. Various new advances have been made to diagnose gynecological pathologies which include imprint cytology and frozen sections in addition to the histopathological techniques. The aim of the study was to assess the diagnostic accuracy of intraoperative diagnostic procedure with gold standard histopathology.Method The study included 50 patients who had suspected gynecological neoplasm in a time period of 12 months. Their intraoperative diagnosis was made on frozen section and imprint cytology to rule out benign or malignant lesions and compared with gold standard histopathology.Results Our study concludes that maximum cases of female genital tract neoplasms belonged to the age group of 19 to 76 years, with 60% cases in postmenopausal age group. Overall diagnosis of 62, 52, and 76% malignancies were made on imprint cytology, frozen section, and histopathological examination, respectively.Conclusion The study concludes that diagnostic accuracy by intraoperative imprint cytology is higher (80%) than frozen section (76%). True positive cases were maximally reported by histopathology. True negative and false positive cases were equally reported by both frozen and imprint cytology. False negative cases were reported by frozen section more than by imprint cytology. The kappa statistical value was lesser in frozen versus histopathology and more in imprint versus histopathology. The sensitivity, specificity, positive predictive value, and negative predictive value for imprint cytology were 77.5, 90.0, 96.9, and 50%, respectively, whereas for frozen section, it was 72.5, 90.0, 96.7, and 45.0%, respectively.
Keywords: frozen; imprint cytology; sensitivity